The genus Alexeter Förster (Hymenoptera, Ichneumonidae) in China, with descriptions of three new species - Li, Tao; Sun, Shu-Ping (European Journal of Taxonomy, 2022)
Three new species of Alexeter Förster, 1869 are reported from China, A. flavicoxa Li & Sun sp. nov. collected from Sichuan, A. flaviventris Li & Sun sp. nov. from Beijing, Guizhou and A. melanicus Li & Sun sp. nov. from Guizhou. A key to species of Alexeter known in China is provided.